Characterization of Myocardial Microstructure and Function in an Experimental Model of Isolated Subendocardial Damage. Issue 2 (August 2019) - Beyhoff, Niklas; Lohr, David; Foryst-Ludwig, Anna; Klopfleisch, Robert; Brix, Sarah; Grune, Jana; Thiele, Arne; Erfinanda, Lasti; Tabuchi, Arata; Kuebler, Wolfgang M.; Pieske, Burkert; Schreiber, Laura M.; et al.
Abstract : Subendocardial damage is among the first cardiac manifestations of hypertension and is already present in asymptomatic disease states. Accordingly, markers of subendocardial impairment may facilitate early detection of cardiac damages and risk stratification under these conditions. This study aimed to investigate the impact of subendocardial damage on myocardial microstructure and function to elucidate early pathophysiologic processes and to identify corresponding diagnostic measures. Mice (n=38) were injected with isoproterenol to induce isolated subendocardial scarring or saline as corresponding control. Cardiac function and myocardial deformation were determined by high-frequency echocardiography. The cardiac stress response was assessed in a graded exercise test and during dobutamine stress echocardiography. Myocardial microstructure was studied ex vivo by 7 T diffusion tensor magnetic resonance imaging at a spatial resolution of 100×100×100 µm3 . Results were correlated with histology and biomarker expression. Subendocardial fibrosis was accompanied by diastolic dysfunction, impaired longitudinal deformation (global peak longitudinal strain [LS]: −12.5±0.5% versus −15.6±0.5%; P <0.001) and elevated biomarker expression (ANP [atrial natriuretic peptide], Galectin-3, and ST2). Systolic function and cardiac stress response remained preserved. Diffusion tensor magnetic resonance imaging revealed a left-shift in helix angle towards lower values in isoproterenol-treated animals, which was mainly determined by subepicardial myofibers (mean helix angle: 2.2±0.8° versus 5.9±1.0°; P <0.01). Longitudinal strain and subepicardial helix angle were highly predictive for subendocardial fibrosis (sensitivity, 82%–92% and specificity, 89%–90%). The results indicate that circumscribed subendocardial damage alone can cause several hallmarks observed in cardiovascular high-risk patients. Microstructural remodeling under these conditions involves also remote regions, and corresponding changes in longitudinal strain and helix angle might serve as diagnostic markers. Abstract : Supplemental Digital Content is available in the text.